Kontribusi “Pemmali” Tanah Bugis bagi Pembentukan Akhlak - Muhammah Rusli; Rakhmawati Rakhmawati (UIN Maulana Malik Ibrahim Malang, 2013)
Pemmali culture has firmly staked in Bugis cultural traditions through speech and is believed to shape children’s morals to anticipate the negative effect of the surroundings. Parents introduced pemmali to their children from an early age before they get formal education. Selection of appropriate phrases or sentences easily understood by younger children is the key for parenting success in transmitting noble values. An easy word, for instance, ulcers, worms, bad luck, insurgent, hit by something or kidnapped by demon, lack of sustenance, orphaned, struck by lightning, do not get a mate, and the other can affect children’s way of thinking so that they accept their parent’s advice. The consequence of pemmali is very effective in influencing the thinking and behavior of Bugis children to adulthood. Pemmali reflects noble values inherited from generation to generation. It contains the value of prudence warns for the children to act, customary manners in daily life; appreciating parents, teachers, and human beings; managing time, building mental and physical health and creativity of the children, and others. The concept of pemmali is a main choice for Bugis parents to anticipate the negative effects of globalization era. It expresses the local values as part of national culture. Budaya pemmali telah mengakar dalam tradisi suku Bugis melalui budaya tutur dan diyakini mampu membentuk akhlak anak serta mengantisipasi pengaruh negatif lingkungannya. Pemmali diperkenalkan orang tua Bugis kepada anak-anaknya sejak dini sebelum mereka mengenal dunia pendidikan formal. Pemilihan kata atau kalimat yang pas dan mudah dipahami anak usia dini merupakan kunci kesuksesan orang tua Bugis dalam mewariskan nilai-nilai luhur dan akhlak yang baik kepada anak-anaknya. Kata bisulan, cacingan, celaka, durhaka, ditabrak atau diculik setan, kurang rezeki, orang tua meninggal, disambar petir, tidak mendapatkan jodoh, dan lainnya merupakan kata yangmudah mempengaruhi cara berpikir mereka sehingga mau menerima nasehat orang tuanya. Konsekuensi pemmali sangat efektif mempengaruhi cara berpikir dan perilaku anak Bugis sampai dewasa. Sebagai budaya, pemmali syarat akan nilai-nilai luhur yang diwariskan secara turun temurun. Di dalamnya terkandung nilai kehati-hatian bagi anak dalam bertindak, adat sopan santun dalam menjalani kehidupan sehari-hari; penghargaan kepada orang tua, guru, dan sesama manusia; manajemen waktu, membangun kesehatan mental, fisik dan kreatifitas anak, dan lainnya. Kini konsep pemmali menjadi pilihan utama orang tua Bugis dalam mengantisipasi derasnya pengaruh negatif era globalisasi pada anaknya. Ini merupakan ekspresi kearifan lokal sebagai bagian budaya nasional.